Efficacy of Prophylactic Antibiotic Timing and Duration in Preventing Surgical Site Infections After Elective Abdominal Surgery: A Meta-Analysis of Randomized Controlled Trials - Qavi, Qasif; Shahi, Ameena; Syeda, Laveeza; Lama, Yeshe; Janee, Rafsan; Ali, Waniza; Haleem, Rozal; Akram, Ayesha; Aziz, Usama; Nixon, Cathrine; et al. (Journal of Neonatal Surgery, 2025)
Background: Surgical site infections (SSIs) are a leading cause of postoperative morbidity and healthcare expenditure, particularly in abdominal surgeries. While prophylactic antibiotics are essential in reducing infection risk, the optimal timing and duration of administration remain uncertain. This meta-analysis aims to evaluate the efficacy of different antibiotic timing and duration strategies in preventing SSIs during elective abdominal and pelvic surgeries. Methods: This study followed PRISMA guidelines and included randomized controlled trials (RCTs) comparing different timing (pre-incision vs. intraoperative/post-cord clamping) and durations (24-hour vs. extended regimens) of prophylactic antibiotics. A systematic search was conducted across PubMed, Scopus, Embase, Cochrane CENTRAL, and Web of Science up to July 2024. Risk of bias was assessed using the Cochrane RoB 2.0 tool, and statistical analyses were performed using RevMan 5.4 with a random-effects model. Results: Three RCTs involving 1,999 patients were included. Pre-incision administration of antibiotics significantly reduced SSI rates compared to post–cord clamping (RR = 0.14; 95% CI: 0.04 to 0.53; p < 0.01). No significant difference was observed between preoperative and intraoperative administration (RD = –1.3%; 95% CI: –4.1% to +6.7%). For duration, a 24-hour regimen was non-inferior to extended use (RD = –3.8%; 95% CI: –11.1% to +3.4%), supporting shorter prophylactic courses. Conclusion: Pre-incision antibiotic administration is superior to delayed dosing in preventing SSIs. A 24-hour antibiotic regimen is as effective as extended courses, offering benefits for antimicrobial stewardship without compromising clinical outcomes. These findings support global recommendations to standardize perioperative antibiotic protocols and reduce unnecessary antibiotic exposure.